MicroRNA‐21 antisense oligonucleotide improves the sensitivity of A375 human melanoma cell to Cisplatin: An in vitro study. Issue 4 (4th January 2018) - Zhang, Hai‐Lin; Si, Lou‐Bin; Zeng, Ang; Long, Fei; Qi, Zheng; Zhao, Ru; Bai, Ming
Abstract: This study explored Cisplatin resistance effect of microRNA‐21 (miR‐21) antisense oligonucleotide (AS‐ODN) in human melanoma A375 cell. AS‐ODN was transfected in melanoma A375 cells and Cisplatin‐resistant cell line A375/CDDP, and divided into the AS‐ODN, nonsense oligonucleotide (NS‐ODN) and normal groups. Cell ultrastructure changes were observed through transmission electron microscope. MiR‐21 AS‐ODN could be tested cell growth effect in different time periods by trypan blue exclusion. MiR‐21 mRNA expression change was detected by quantitative fluorescence PCR. Cell apoptosis, cycle distribution and miR‐21 AS‐ODN effect on proliferation and Cisplatin sensitivity were tested by flow cytometry, MTT assay, TUNEL, and Clonogenic assay. Cell apoptosis was observed after transfection 24 h with the AS‐ODN group, while the NS‐ODN and normal group cells had no apoptotic symptoms; Compared with the normal group, the AS‐ODN group began to show obvious cell growth inhibition effect after transfection 24 h lasting 72 h (all P < 0.05), but the NS‐ODN group had no significant difference ( P > 0.05). miR‐21 mRNA expression in the AS‐ODN group was obviously decreased with rising apoptosis rate (all P < 0.05) and there was no significant difference in the NS‐ODN group ( P > 0.05). MiR‐21 AS‐ODN could remarkably increase A375 cell and A375/CDDP cell sensitivity to Cisplatin ( P < 0.05), while A375 cell sensitivity to Cisplatin between the NS‐ODN group and the normal group had no difference. MiR‐21 AS‐ODN decreased IC50 and increased Cisplatin sensitivity for A375 cells and A375/CDDP cells, which would be a new target of melanoma treatment. Abstract : MiR‐21 AS‐ODN decreased IC50 and increased Cisplatin sensitivity for A375 cells and A375/CDDP cells, which would be a new target of melanoma treatment.